2018
DOI: 10.1371/journal.pone.0205576
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies and meta-analysis uncovers new candidate genes for growth and carcass traits in pigs

Abstract: Genome-wide association studies (GWAS) have been widely used in the genetic dissection of complex traits. As more genomic data is being generated within different commercial or resource pig populations, the challenge which arises is how to collectively investigate the data with the purpose to increase sample size and implicitly the statistical power. This study performs an individual population GWAS, a joint population GWAS and a meta-analysis in three pig F2 populations. D1 is derived from European type breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Most of the clusters overlapped or were in the vicinity of the previously reported QTL. This was expected as the database has been recently updated and also includes our previous results (Blaj et al 2018) using SNP chip data and three out of the four pig populations which were taken into account here. Some of the earlier reported QTL in the database spread over large genomic regions ( e.g.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Most of the clusters overlapped or were in the vicinity of the previously reported QTL. This was expected as the database has been recently updated and also includes our previous results (Blaj et al 2018) using SNP chip data and three out of the four pig populations which were taken into account here. Some of the earlier reported QTL in the database spread over large genomic regions ( e.g.…”
Section: Discussionmentioning
confidence: 56%
“…, stable, slaughter month) and for the effect of RYR1 gene (Fujii et al 1991) using a general linear model. Trait definition, descriptive statistics and information about the pre-adjustment and the fixed effects used per cross can be found in (Blaj et al 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we combined the results of GWAS from two resource populations: an F2 design and one half-sib (HS) population divergently selected for feather pecking behavior. This type of meta-analysis was already established in pigs [11] and applied in an FP analysis, which in addition included selection signatures [8]. The same strategy enabled us to identify 15 genome-wide significant variants associated with FP behavior in the present study.…”
Section: Introductionmentioning
confidence: 97%
“…The most significant SNP (rs80983858) located at the 3255-bp downstream of positional candidate gene GRM4 , and the G allele was of benefit to increase facial wrinkles. Previously at around 34.8 Mb on SSC7, we have also identified QTLs affecting ear size [7], meat moisture content [17], skin thickness [18], fatness deposition [19], the weight of internal organs [12], limb bone lengths [20], head weight [21], and carcass length [22] in divergent pig populations, which indicated that this candidate region plays important roles in the development of many traits in pigs. This region is a gene-rich region, for example, there were 35 protein-coding genes from 34.0 to 35.5 Mb on SSC7, which suggested that the biological functions of this locus would be very important and complicate.…”
Section: Discussionmentioning
confidence: 99%